Structural and evolutionary relationships among five members of the human gamma-crystallin gene family. - Meakin, S O (1985)
We have characterized five human gamma-crystallin genes isolated from a genomic phage library. DNA sequencing of four of the genes revealed that two of them predict polypeptides of 174 residues showing 71% homology in their amino acid sequence; the other two correspond to closely related pseudogenes which contain the same in-frame termination codon at identical positions in the coding sequence. Two of the genes and one of the pseudogenes are oriented in a head-to-tail fashion clustered within 22.5 kilobases. All three contain a TATA box 60 to 80 base pairs upstream of the initiation codon and a highly conserved segment of 44 base pairs in length immediately preceding the TATA box. The two genes and the two pseudogenes are similar in structure: each contains a small 5' exon encoding three amino acids followed by two larger exons that correspond exactly to the two similar structural domains of the polypeptide. The first intron varies from 100 to 110 base pairs, and the second intron ranges from 1 to several kilobases, rendering an overall gene size of 1.7 to 4.5 kilobases. At least one of the two pseudogenes appears to have been functional before inactivation, suggesting that their identical mutation was generated by gene conversion.